Phylogeography of two closely related Indo-Pacific butterflyfishes reveals divergent evolutionary histories and discordant results from mtDNA and microsatellites - Di Battista, Joseph; Rocha, L.; Craig, M.; Feldheim, K.; Bowen, B. (Oxford Journals, 2012)
Marine biogeographic barriers can have unpredictable consequences, even among closely related species. To resolve phylogeographic patterns for Indo-Pacific reef fauna, we conducted range-wide surveys of sister species, the scrawled butterflyfish (Chaetodon meyeri; N = 134) and the ornate butterflyfish (Chaetodon ornatissimus; N = 296), using mitochondrial DNA cytochrome b sequences and 10 microsatellite loci. The former is distributed primarily in the Indian Ocean but also extends to the Line Islands in the Central Pacific, whereas the latter is distributed primarily in the Central-West Pacific (including Hawaii and French Polynesia) but extends to the eastern margin of the Indian Ocean. Analyses of molecular variance and Bayesian STRUCTURE results revealed 1 range-wide group for C. meyeri and 3 groups for C. ornatissimus: 1) eastern Indian Ocean and western Pacific, 2) Central Pacific, and 3) Hawaii. Estimates of the last population expansion were much more recent for C. meyeri (61 500 to 95 000 years) versus C. ornatissimus (184 700 to 286 300 years). Despite similarities in ecology, morphology, life history, and a broadly overlapping distribution, these sister species have divergent patterns of dispersal and corresponding evolutionary history. The mtDNA and microsatellite markers did not provide concordant results within 1 of our study species (C. meyeri), or in 7 out of 12 other cases of marine fishes in the published literature. This discordance renews caution in relying on one or a few markers for reconstructing historical demography. © 2012 The American Genetic Association. All rights reserved.